Fertilization with urea, ammonium and nitrate produce different effects on growth, hydraulic traits and drought tolerance in Pinus taeda seedlings - Faustino, Laura Inés (2015)
Urea fertilization decreases Pinus taeda L. growth in clay soils of subtropical areas. The negative effect of urea is related to changes in some hydraulic traits, similar to those observed in plants growing under drought. The aims of this work were (i) to determine whether different sources of nitrogen applied as fertilizers produce similar changes in growth and hydraulic traits to those observed by urea fertilization and (ii) to analyze the impact of those changes in plant drought tolerance. Plants fertilized with urea, nitrate (NO3-) or ammonium (NH4+) were grown well watered or with reduced water supply. Urea and NO3- fertilization reduced plant growth and increased root hydraulic conductance scaled by root dry weight (DW). NH4+ fertilization did not reduce plant growth and increased shoot hydraulic conductance and stem hydraulic conductivity. We conclude that NO3- is the ion involved in the changes linked to the negative effect of urea fertilization on P. taeda growth. NH4+ fertilization does not change drought susceptibility and it produces changes in shoot hydraulic traits, therefore plants avoid the depressive effect of fertilization. Urea and NO3- fertilizers induce changes in DW and root hydraulic conductance and consequently plants are less affected by drought.